Sant’Ambrogio e San Martino - Domokos, György (Verbum – Analecta Neolatina, 2017)
The goal of the short paper is to point out parallelisms between the lives and cults of two saints of the 4th century, Martinus and Ambrosius. They both were bishops of important cities and defenders of catholic orthodoxy against Arian heresy. The apsidal mosaic of the Milanese St. Ambrosius basilica from the 9th century as well as the golden altar of the same church represent a curious scene with the aim of linking together the two personalities. We can point out that it is just in this period that the cult of Martinus is becoming a symbol of the emerging Caroling empire even in the far away native city of Savaria (today’s Szombathely in Hungary), and so the representation of Ambrosius also meant the linking the city of Milan to the Empire.